Poems - Feinman, Alvin, 1929-2008 (Book collections on Project MUSE., 1990)
This volume of Alvin Feinman's poems presents a highly praised earlier work, Preambles and Other Poems, combined with more recent poems. Of Preambles Allen Tate wrote, "This is a remarkable first book. ... There is an acute and subtle sensibility at work. 'Pilgrim Heights' is one of the best poems by an American that I have seen in many years.' "From "Pilgrim Heights"Something, something, the heart hereMisses, something it knows it needsUnable to bless--the wind passes;A swifter shadow sweeps the reeds, The heart a colder contrast brushes. So this fool, face-forward, bellyPressed among the rushes, plays outHis pulse to the dune's long slantDown from blue to bluer element, The bold encompassing drink of airAnd namelessness, a length compoundOf want and oneness the shore's mumblingDistantly tells--something a wing'sDry pivot stresses, carvedThrough barrens of stillness and glare. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905